The Contribution of Sustained Attention and Response Inhibition to Reading Comprehension Among Japanese Adolescents - Inbar Lucia Trinczer; Yarden Dankner; Shira Frances-Israeli; Yoshi A. Okamoto; Dav Clark; Lilach Shalev (MDPI AG, 2024)
Background: Previous studies demonstrated the influential role of sustained attention in the reading comprehension of alphabetic writing systems. However, there is limited understanding of how these cognitive functions contribute to reading comprehension in non-alphabetic systems, such as Japanese. This study seeks to explore this gap, focusing on how sustained attention and response inhibition function in a writing system where some of the characters represent meanings rather than sounds, introducing another layer of difficulty in the complex process of reading; Methods: Seventy-five Japanese 9th grade students performed a task to assess sustained attention and response inhibition. The cognitive test was carried out using tablets to enable feasible parallel group administration while maintaining high comparability with ecological classroom settings. Reading comprehension was measured using an exam that the participants took as part of their educational routine; Results: Our results indicate that both sustained attention and response inhibition significantly contributed to the reading comprehension of Japanese 9th grade students; Conclusions: These results replicate and expand previous studies documenting the contribution of sustained attention on the reading comprehension of alphabetic writing systems to a non-alphabetic system. Moreover, our findings unravel another important cognitive factor, namely response inhibition in reading comprehension. We suggest that response inhibition may play a crucial role in reading non-alphabetic writing systems that pose high cognitive demands, such as Japanese.